Treatment of alcohol dependence - Hanwella, Raveen; De Silva, V. (Ceylon Medical Journal, 2009)
It is important to manage alcohol withdrawal properly. Mismanagement could lead to permanent brain damage or even death. The principles are simple and easily learnt. New pharmacological agents have come into use which helps in maintaining abstinence. Clinicians should update themselves on their use.
Keywords: Alcohol dependence; treatment